2019
DOI: 10.1039/c9ra09678g
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable preparation of sunlight active α-Fe2O3nanoparticles using iron containing ionic liquids for photocatalytic applications

Abstract: Inspired by nanosegregation of ionic liquids into bicontinuous structures of arrays of ionic and non-ionic components, we present a new sustainable strategy for preparation of mesh-like nano-sheets of α-Fe2O3 nanoparticles and their photocatalytic activity under sunlight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
(109 reference statements)
0
8
0
Order By: Relevance
“…ILBSs have been explored in various fields, including chemical synthesis and catalysis [ 165 , 166 , 167 , 168 , 169 , 170 ], drug delivery [ 171 , 172 , 173 , 174 , 175 , 176 , 177 ], biomass conversion [ 178 , 179 , 180 , 181 , 182 , 183 ], liquid crystal development [ 184 , 185 , 186 ], decontamination [ 187 , 188 , 189 , 190 , 191 , 192 , 193 ] and formation and stabilization of metal NPs [ 61 , 194 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 …”
Section: Applications Of Il-based Surfactantsmentioning
confidence: 99%
See 3 more Smart Citations
“…ILBSs have been explored in various fields, including chemical synthesis and catalysis [ 165 , 166 , 167 , 168 , 169 , 170 ], drug delivery [ 171 , 172 , 173 , 174 , 175 , 176 , 177 ], biomass conversion [ 178 , 179 , 180 , 181 , 182 , 183 ], liquid crystal development [ 184 , 185 , 186 ], decontamination [ 187 , 188 , 189 , 190 , 191 , 192 , 193 ] and formation and stabilization of metal NPs [ 61 , 194 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 …”
Section: Applications Of Il-based Surfactantsmentioning
confidence: 99%
“…To limit the use of organic solvents, and to reduce the number of preparation steps, Komal et al [ 205 ] used ILBSs with tetrachloroferrate anion, namely, 1-R-3-methylimidazolium FeCl₄, R = n-butyl, n-octyl and n-hexadecyl as the templates for the preparation of α-Fe 2 O 3 NPs, via a grinding followed by calcination. It was observed that upon going from n-butyl to n-hexadecyl, the size of the NPs decreases.…”
Section: Applications Of Il-based Surfactantsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, its low conductivity, short carrier diffusion length and relatively high potential, limit the saturation current and current development potential [14]. α-Fe 2 O 3 is prepared by methods such as chemical vapor deposition (CVD) [15][16][17], spray pyrolysis [18], hydrothermal methods [19], and precipitation [20]. Shape, size, surface structure and microstructure are the main factors which affect the chemical and physical properties of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%